CREDIT-MODULE SYSTEM: FEATURES AND OPPORTUNITIES - Ishankhadjaeva Feruza Abduboriyevna (Journal of Higher Education and Academic Advancement, 2024)
This article is about the currently developing credit module system. It is about adapting the education system in our country to the world system.